Hair Assays for Drugs of Abuse in a Probation Population: Pilot Study in a Florida Correctional Field Setting, 1993 - Mieczkowski, Tom ([Verlag nicht ermittelbar], 1997)
The major objectives of this research project were: (1) to evaluate the effectiveness of the combination of hair and urine assays in determining drug use among probationers, (2) to examine the concordance patterns of hair and urine specimens, (3) to explore the perceptions and attitudes of probation officers regarding the use of hair assays for drug testing, and (4) to assess the feasibility of implementing hair analysis in a probationary field setting. The 22 correctional officers who participated in this study were recruited from the Florida Department of Corrections Probation Field Services Divisions, and worked within Pinellas and Pasco counties. Each officer was requested to solicit from his or her caseload eight to ten probationers who would be eligible for the project because they would be undergoing at least monthly urinalysis or urine testing. Approximately 150 probationers participated in the project and were subject to hair assays for illicit drug use, along with standard urine testing. Specimens were collected and analyzed on 90 probationers over a six-month period and on 101 probationers for five consecutive months, as well as fewer numbers of samples for the other probationers. The drugs for which the hair and urine specimens were analyzed included cocaine, opiates, cannabinoids such as marijuana, PCP, and methadone. Survey questions asked of the probation officers (Part 1) covered personal information (gender, ethnicity, education level, years of experience in corrections, and satisfaction with job) and attitudes and opinions about their jobs and drug testing (estimated percentage of caseload using drugs, whether all clients should be tested, and whether knowing drug quantities is helpful). Data in Part 2 cover probationers' drug test results and self-reported drug use, personal information (gender, age, weight, ethnicity, and criminal charge), a variety of hair questions (color, texture, style, length, how often shampooed, and if dyed, tinted, bleached, relaxed, or jeried), and use of medications, along with the medication name and amount.